The Soil and Water Assessment Tool (SWAT) Model in the Context of Erosion Monitoring in the Batulayar Sub-Watershed Area - Mujiono, Ikha Setiawaty; Ayuba, Sri Rahayu; Jaya, Risman (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
This study was conducted in the Batulayar Sub-Watershed, Distrik Bongomeme, with the aim of assessing the level of erosion and evaluating the SWAT model as a tool for erosion monitoring. A mixed-method approach was employed, with data analyzed using the ArcSWAT software. The results indicated that the Batulayar Sub-Watershed experienced erosion categorized as "very mild" and "mild," ranging from 0-15 tons/ha/year to 15-60 tons/ha/year, according to the classification by the Ministry of Forestry. Very mild erosion occurred in 15 sub-basins, primarily in areas with flat to moderately steep slopes, while mild erosion was observed in 29 sub-basins with steeper slopes. The main factors contributing to erosion were slope gradient, soil type, and land use, particularly agricultural activities on steep slopes. Calibration and validation results showed an NSE value of 0.9, indicating a high level of accuracy in replicating observed discharge. The SWAT model proved effective in mapping the distribution of erosion levels and provided critical insights for sustainable soil and water conservation management.